Sleep Neurology - A Wakeup Call for Neurologists. Issue 1 (1st February 2002) - Berkovic, Samuel F.; King, Philip
Abstract : Sleep medicine is an exploding field and yet the disorders of sleep, and the effects of sleep on many neurological disorders, have been largely ignored by the neurological community. This has both patient care and medico-political implications. Amongst those who first described sleep apnoea was the great French neurologist Henri Gastaut. Whilst several groups, including neurologists, have maintained interest in neurological sleep disorders since those early days, the neurological fraternity has been remiss in not embracing sleep neurology with greater gusto. Patients with neurological sleep problems are poorly served overall by our discipline. Recognition that sleep apnoea is a very common and treatable sleep disorder has resulted in the practice of sleep medicine being dominated by respiratory physicians. Much has been learned about sleep apnoea; this condition and disorders that may mimic it are skilfully managed in many respiratory orientated laboratories. However, in many countries there has been a promulgation